The Effect of Giving Boiled Chicken Eggs on the Healing of Perineal Wounds for Postpartum Mothers in the Independent Practice of Midwife Sumiariani in 2021 - Jujuren Sitepu; Rista Buana Gultom (Formosa Journal of Science and Technology, 2022)
Postpartum infections still play a role as the main cause of maternal death, especially in developing countries like Indonesia. The aim of this study was to determine the effect of giving boiled chicken eggs on perineal wound healing in postpartum women. The type of research used in this study was a Quasi Experiment with a population of postpartum women with perineal wounds with a total sample of 10 respondents, 5 respondents (intervention group) and 5 respondents (control group). The results of the study showed that the average length of days healing of perineal wounds in postpartum women in the intervention group (given boiled eggs) was 5.4 days. The mean duration of perineal wound healing in the control group was 10.6 days. There is an effect of giving boiled chicken eggs on perineal wound healing in postpartum women with a p-value of 0.000 <0.05.